Oral health of adults in Northern Norway – a pilot study - Adekoya, Sarah Moriye (Universitetet i Tromsø, 2012)
There is a deficiency of data on oral health of adults in northern Norway, and available reports indicate poorer oral health in the north as compared with the rest of the country. The objective of this pilot study was to develop and test out tools for a larger epidemiological study of oral health among adults in northern Norway. The study was conducted in the municipalities of Nordkapp and Båtsfjord located in the northernmost county, Finnmark. Questionnaires and letters of invitation were sent to 100 randomly selected individuals in each town, in total 200. Those who filled and returned the questionnaires were sent appointment cards to a free oral examination at the local dental clinic. The main finding from the study was a low response rate; 34% responded to the questionnaire and 26.5% attended the oral examination. Response rate was highest among women above forty years old (37%) and lowest among men under forty years (12%). There is a necessity for further studies and the need to find strategies to increase response rate to subsequent oral epidemiologic studies in northern Norway. Radiological examination is not necessary for such studies but a questionnaire and a physical oral examination should be included.